Singapore Management University Report to Stakeholders 2004 - 2005 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2004)
As the Singapore Management University moves into the Singapore centre, a whole new interchange between education and city takes hold in this revitalised urban environment. Bridging the scholastic origins of Bras Basah with the promise of the new millennium, SMU is at the centre of a new and dynamic educational hub where foundations are being readapted and the future redefined. Every facet of the SMU experience – academic programmes and research, faculty and staff enterprise, student activity and exploration – embraces the University’s passion for creativity, personal interchange and bold challenge.